2017
DOI: 10.1103/physrevd.95.074502
|View full text |Cite
|
Sign up to set email alerts
|

Chiral separation effect in lattice regularization

Abstract: We consider Chiral Separation Effect (CSE) in the lattice regularized quantum field theory. We discuss two types of regularization -with and without exact chiral symmetry. In the latter case this effect is described by its conventional expression for the massless fermions. This is illustrated by the two particular cases -of Wilson fermions and of the conventional overlap fermions. At the same time in the presence of the exact chiral symmetry the CSE disappears. This is illustrated by the naive lattice fermions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 60 publications
2
65
0
Order By: Relevance
“…In the present paper we proceed with the development of Wigner-Weyl formalism for the tight-binding models of solid state physics (or, equivalently, for the lattice regularized quantum field theory). We extend the previous works made in this direction 27,28,29,30,31,32,55,56,54 . The developed technique is applied to the class of the inhomogeneous models that includes, in particular, the tight-binding model of graphene in the presence of both inhomogeneous magnetic field and nontrivial elastic deformations.…”
Section: Conclusion and Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In the present paper we proceed with the development of Wigner-Weyl formalism for the tight-binding models of solid state physics (or, equivalently, for the lattice regularized quantum field theory). We extend the previous works made in this direction 27,28,29,30,31,32,55,56,54 . The developed technique is applied to the class of the inhomogeneous models that includes, in particular, the tight-binding model of graphene in the presence of both inhomogeneous magnetic field and nontrivial elastic deformations.…”
Section: Conclusion and Discussionsupporting
confidence: 65%
“…It has been used in the field-theoretic kinetic theory 20,21 , in noncommutative field theories 22,23 . Certain applications of the Wigner-Weyl formalism were proposed to several fields of theoretical physics including cosmology 24,25,26 . The Wigner-Weyl formalism has been widely applied to the study of nondissipative transport phenomena 27,28,29,30,31,32 . Using this formalism it has been shown that the response of nondissipative currents to the external field strength is expressed through the topological invariants that are robust to the smooth deformation of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the works of one of the authors of the present paper the Wigner-Weyl formalism has been applied to the study of the nondissipative transport phenomena [47][48][49][50][51][52]. In particular, it was shown that the response of nondissipative currents to the external field strength is expressed through the topological invariants that are robust to the smooth deformations of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The only lattice studies we are aware of are related to the investigation of the chiral separation effect in a relativistic Dirac plasma [57][58][59]. However, it is still unknown whether the chiral analog of the BZCS term can be derived in the lattice models and whether it enjoys the same topological robustness as its counterpart in the electric current.…”
Section: Introductionmentioning
confidence: 99%